Kinematics analysis of the undulatory underwater swimming during a grab start of national level swimmers - Houel, N.; Elipot, M.; Andree, F; Hellard, P (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Few information clearly present the important factor that the swimmer should achieve to limit the loss of velocity during the underwater phase of a start. The aim of this study is to estimate the most important factors that the swimmers would use to improve his performance. METHOD: Twelve swimmers were asked to perform acompetitive start. The underwater area was recorded using three cameras. A modified double plane direct linear transformation method was used to calculate the landmark coordinates in space. The following variables were defined: the horizontal velocity of the center of mass (Vxg) and hip (Vxh); the angle of attack of trunk (átr), thigh (áth), leg (ále), foot (áfo); the mean kick frequency (f ); the mean kick amplitude (A); the phase time of the knee (Pk) and the ankle (Pa). The effect of the independent variables (átr, áth, ále, áfo, f, A, Pk,Pa) on the dependent variables Vxg and Vxh was analysed using stepwise linear regression. RESULTS: The regression equations show that different parameters influence Vxg and Vxh at different phase of the underwater undulatory swimming. Between 5.5 to 6.5 m, the stepwise regression analysis show that the decrease of angles of attack of different segments (átr at 5.5 m, áfo at 6 m, áth at 6.5 m) are selected variables to improve the horizontal velocity Vxg and Vxh. Between 6 to 7.5 m, the stepwise regression analysis show that the increase of the phase time (Pk and Pa) are selected variables to improve the horizontal velocity Vxg and Vxh. At 6.5 m, the stepwise regression analysis show that the decrease of the angles of attack of thigh (áth) and the increase of the phase time of the knee (Pk) are the best predictors to improve horizontal velocity Vxg and Vxh (R2=0.79 for Vxg and R2=0.89 for Vxh). At 7.5 m, the stepwise regression analysis show that increase of phase time of the knee (Pk) and mean kick frequency (f ) are the selected variables to improve respectively Vxg and Vxh DISCUSSION: At 6.5 m, the decrease of the angle of attack of the thigh (áth) and the increase of the phase time of the ankle (Pa) predicts the improvement of the horizontal velocity Vxg and Vxh. The stepwise regressions enable to propose principles to improve the underwater phase of the swimmer of the present study: to adopt streamline position with linear adjustment of the trunk and the bottom segments, to move like dolphins using only foot and leg for propulsive segment in underwater undulatory swimming.